Source Apportionment and Health Risk Assessment of Heavy Metals in Endemic Tree Species in Southern China: A Case Study of Cinnamomum camphora (L.) Presl - Li, Ning; Li, Yan; Zhou, Shenglu; Zhang, Huanchao; Wang, Genmei (Frontiers in Plant Science, 2022)
As a developed economic region in China, the problem of heavy metals (HMs) pollution in the Yangtze River Delta has become increasingly prominent. As an important evergreen broad-leaved tree species in southern China, camphor tree can not only be used as a street tree, but also various tissues and organs can be used as raw materials for Chinese herbal medicine. In order to explore the pollution status of HMs in camphor trees in Yixing City in the Yangtze River Delta region, the bark and leaves of the most commonly used medicinal parts of camphor trees were collected. Based on the determination of HMs content, the health risks after human intake are evaluated, the sources and contributions of HMs are analyzed, and then the health risks of pollution sources are spatially visualized. The results showed that, under the influence of human activities, the camphor trees in the study area had obvious enrichment of HMs, and the over standard rate of Pb in the bark was as high as 90%. The non-carcinogenic risks of bark and leaves are acceptable, but the carcinogenic risks are not acceptable. The bark had the highest average carcinogenic risk, approaching 6 times the threshold. The results of Pb isotope ratio analysis showed that the average contribution rate of industrial activities to HMs in camphor trees in the study area was the highest, reaching 49.70%, followed by fossil fuel burning (37.14%), and the contribution of natural sources was the smallest, only 13.16%. The locations of the high-risk areas caused by the three pollution sources to the study area are basically similar, mainly concentrated in the northwest, northeast and southeast, which is consistent with the distribution of industries and resources in the study area. This study can provide scientific guidance for the precise prevention and control of HMs pollution in camphor trees in the study area.